Women who received varicella vaccine versus natural infection have different long-term T cell immunity but similar antibody levels. Issue 7 (11th February 2020) - Tourtelot, Ellen; Quataert, Sally; Glantz, J. Christopher; Perlis, Lauren; Muthukrishnan, Gowrishankar; Mosmann, Tim
Highlights: Higher level of VZV specific CD4 T cells in chickenpox versus vaccinated cohort. Similar median VZV antibody titers in chickenpox versus vaccinated cohort. Chickenpox cohort had higher cell-mediated immune responses to both VZV-infected cell lysate and VZV IE-62 peptides versus the vaccinated cohort. Abstract: Background: Varicella-zoster virus (VZV) infection during pregnancy is associated with serious fetal anomalies. The live-attenuated VZV vaccine was approved in 1995, so many vaccinated women are now of childbearing age. The question of long-term immunity to varicella is critical because breakthrough chickenpox can occur after vaccination. Objective: To compare humoral and T cell immunity between women of childbearing age who were immunized by vaccination or chickenpox disease. Study design: Non-pregnant females between 18 and 36 years old with a history of VZV immunization (n = 20) or prior chickenpox disease (n = 20) were recruited. IgG antibody titers and T cell responses were measured by flow cytometry-based methods in serum and peripheral blood, respectively. Results: There were no significant differences in median antibody titers between vaccinated and chickenpox groups (p = 0.34). The chickenpox group had significantly higher levels of VZV antigen-specific CD4 T cells (p = 0.004). Conclusion: Natural infection induced higher VZV-specific T cell immune responses than vaccination.